William J. Seymour and the origins of global Pentecostalism : a biography and documentary history - Espinosa, Gastón (Duke University Press, 2014)
In 1906, William J. Seymour (1870-1922) preached Pentecostal revival at the Azusa Street mission in Los Angeles. From these and other humble origins the movement has blossomed to 631 million people around the world. Gastón Espinosa provides new insight into the life and ministry of Seymour, the Azusa Street revival, and Seymour's influence on global Pentecostal origins. After defining key terms and concepts, he surveys the changing interpretations of Seymour over the past 100 years, critically engages them in a biography, and then provides an unparalleled collection of primary sources, al.